Distribution, local use, and bio-prospecting opportunity of Ocimum americanum L. in Northwestern part of the Amhara Region, Ethiopia - Edeget Merawi; Taye Birhanu Belay (Center for Science and Technology, IAIN Surakarta, 2024)
Ocimum americanum (Basil) encompasses various uses. The plant is valued both as a food additive for its aromatic qualities and in folk medicine for treating various ailments. However, its uses, distribution, and the associated community knowledge have not been properly and systematically documented. Therefore, a survey was conducted to explore the bio-prospecting potential of Ocimum americanum and gather baseline information on its community knowledge. Purposive and proportional samplings were used to select districts, villages, users, and growers who participated in the study. The selected districts - Dembiya, Gonder Zuria, Takusa, Alefa, Bahir Dar city, and Bahir Dar Zuria Districts - were selected based on the plant’s growth potential and user availability. Data collection methods included semi-structured interviews, group discussions, and field observations. The findings revealed that basil is used for various purposes: ailment treatment (32.67%), food flavoring (26.6%), food preservative (7.7%), and to impart aroma to different foods (8.33%). Specifically, 32.67 % of the respondents used Ocimum americanum for traditional medicine purposes, primarily to treat depression/headaches, stomach aches, and ward off evil spirits. The methods for preparation and administration included concoction (21.05 %), direct application of plant parts (15.79%), grinding (15.79%), melting (5.26%), Fumigation (10.53%), and inhalation (31.58%). Medicinal dosage varied among users depending on the intensity, type, experience, and the severity of the disease. Nine traditional foods spiced, with basil were identified, with the highest fidelity level for basil use being food flavoring (18.33%) followed by preservation (18.33%). The direct matrix analysis indicated that chilli pepper spice was the most preferred local food sweetened by basil, followed by hot-spiced pepper. This study highlights the traditional foods spiced with basil and providesvaluable insights for bio-prospecting companies in the food and pharmacological industries.